2005
DOI: 10.1002/rra.865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nature-like fishways for re-establishing connectivity in fragmented salmonid populations in the River Emån

Abstract: We evaluated the function of two nature-like fishways for re-establishing connectivity for anadromous salmonids in the regulated River Emån. Between 90 and 100% of the salmonids that entered the fishways actually passed through them, with median speeds of 180-190 m h À1 . Only 50% of the anadromous brown trout that passed the first fishway also passed the second one, indicating that the fish might have had problems locating the upstream fishway. The fishways were also observed to function as a passage for down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 35 publications
3
69
3
Order By: Relevance
“…Since anadromous species have to ascend the stream to return to their spawning grounds, attraction and passage efficiencies for such species are high in most fishways [26]. On the other hand, as freshwater fish species migrate without such a natural drive, their attraction and passage efficiencies may vary among fishways [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since anadromous species have to ascend the stream to return to their spawning grounds, attraction and passage efficiencies for such species are high in most fishways [26]. On the other hand, as freshwater fish species migrate without such a natural drive, their attraction and passage efficiencies may vary among fishways [27].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of passing time through the fishway revealed that 36.8% of the individuals passed the fishway within 1 day, while the rest took longer (Table 3), 26.3% of which stayed in the fishway for more than 10 days. The average passing time ranged from 1.2 h to 1559.4 h, showing species-dependent differences.…”
Section: Efficiency Of the Fishwaymentioning
confidence: 99%
“…Leonardsson et al (2005) verified that certain combinations of spillway and turbine flows were found to be beneficial to guide and pass salmon in the correct upstream route, depending on season. Previous observations that enhanced directional cues could affect the fish migration positively (Mills, 1989) and findings that upstream migration rate could be increased by spills (Arnekleiv & Kraabøl, 1996) or bypass constructions close to turbine outlets (Calles & Greenberg, 2005) indicate that the upstream migration of salmonids can be managed. Consequently, the migration problems found for adult salmon in the regulated part of River Umeälven could be lowered by: (1) construction of a fishway in the turbine outlet, so salmon could easily find an upstream route, (2) regulation of spill flows to secure successful attraction and passage efficiency of the bypass, and (3) reconstruction of the current fish ladder at the dam to improve passage speed and success.…”
Section: Conclusion and Management Implications For Sustaining A Salmentioning
confidence: 97%
“…A more recently introduced alternative to fish ladders are the so-called fishways or bypasses, where streams are created to offer migrating fish an alternative passage up and beyond dams. Although these bypasses are created to mimic natural streams (e.g., Calles and Greenberg 2005), their efficiency is sometimes arguable. For instance, the downstream mouth of the bypasses are commonly and for logistic reasons situated quite far from the dam wall and major water flow.…”
Section: Conservation Issuesmentioning
confidence: 99%